Perceptions of ‘Just Culture’ – The Case of Aircraft Maintenance - Malone, Gavin; Darcy, Colette (Journal of Strategic Innovation and Sustainability, 2019)
This research seeks to explore perceptions of a ‘just culture’ within the aviation maintenance sector. The focus is not on the individual or error but rather the systems and processes in place ensure any errors or occurrences are accurately captured. Historically, the focus in aviation has been on attributing blame for individual human error, whereas in modern times there is increasing recognition of the systems-based approach, which seeks to build a continuous improvement mentality by an inclusive culture that encourages open reporting of incidents without fear of personal reprisal.